Crystal phase regulation of MnO2 for alcohol oxidation with ultra-stability in acidic solution - Junhua Li; Yi Jiang; Ruping Miao; Longfei Yang; Zhiyan Guo; Dawei Chen; Fanglin Du (Catalysis Communications, 2023)
The stability of non-noble metal catalysts for water oxidation is remaining a great challenge in acidic solution. Herein, alcohols oxidation instead of water oxidation coupled with ultradurable H2 production was realized. The MnO2 crystal phase regulation could optimize the electronic structure, and the δ-MnO2 with more Mn3+ showed a higher activity, including a low overpotential of 1.48 V at 50 mA cm−2, and a small Tafel slope of 176.22 mV dec−1. Moreover, the δ-MnO2 catalyst exhibited extremely high stability after 24 h for EG oxidation, while the activity was quickly lost within 0.5 h for water oxidation. This work indicated that crystal phase regulation could improve the active and stability of acidic water splitting catalysts.